Comprehensive Oncologic Imaging in Infants and Preschool Children With Substantially Reduced Radiation Exposure Using Combined Simultaneous 18F-Fluorodeoxyglucose Positron Emission Tomography/Magnetic Resonance Imaging: A Direct Comparison to 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography. Issue 1 (January 2016) - Gatidis, Sergios; Schmidt, Holger; Gücke, Brigitte; Bezrukov, Ilja; Seitz, Guido; Ebinger, Martin; Reimold, Matthias; Pfannenberg, Christina A.; Nikolaou, Konstantin; Schwenzer, Nina F.; Schäfer, Jürgen F.
Abstract : Objective: The aim of this study was to evaluate the clinical applicability and technical feasibility of fluorodeoxyglucose (FDG) positron emission tomography (PET)/magnetic resonance imaging (MRI) compared with FDG PET/computed tomography (CT) in young children focusing on lesion detection, PET quantification, and potential savings in radiation exposure. Methods: Twenty examinations (10 PET/CT and 10 PET/MRI examinations) were performed prospectively in 9 patients with solid tumors (3 female, 6 male; mean age, 4.8 [1–6] years). Fluorodeoxyglucose PET/CT and FDG PET/MRI were performed sequentially after a single tracer injection. Lesion detection and analysis were performed independently in PET/CT and PET/MRI. Potential changes in diagnostic or therapeutic patient management were recorded.  Positron emission tomography quantification in PET/MRI was evaluated by comparing standardized uptake values resulting from MRI-based and CT-based attenuation correction. Effective radiation doses of PET and CT were estimated. Results: Twenty-one PET-positive lesions were found congruently in PET/CT and PET/MRI. Magnetic resonance imaging enabled significantly better detection of morphologic PET correlates compared with CT. Eight suspicious PET-negative lesions were identified by MRI, of which one was missed in CT. Sensitivity, specificity, and accuracy for correct lesion classification were not significantly different (90%, 47%, and 62% in PET/CT; 100%, 68%, and 79% in PET/MRI, respectively).  In 4 patients, the use of PET/MRI resulted in a potential change in diagnostic management compared with PET/CT, as local and whole-body staging could be performed within 1 single examination. In 1 patient, PET/MRI initiated a change in therapeutic management.  Positron emission tomography quantification using MRI-based attenuation correction was accurate compared with CT-based attenuation correction. Higher standardized uptake value deviations of about 18% were observed in the lungs due to misclassification in MRI-based attenuation maps.  Potential reduction in radiation dose was 48% in PET/MRI compared with PET/CT ( P < 0.05). Conclusions: FDG PET/MRI is at least equivalent to FDG PET/CT for oncologic imaging in young children. Specifically, superior soft tissue contrast of MRI results in higher confidence in lesion interpretation. Substantial savings in radiation exposure can be achieved, and the number of necessary imaging examinations can be reduced using PET/MRI compared with PET/CT.